Tratamento cirúrgico das fraturas do odontóide tipo II com parafuso anterior: análise de 15 casos - Dantas, Fernando Luiz Rolemberg (2002)
A retrospective analysis of the results of 15 patients with odontoid fractures type II P and II N, according to Roy-Camille's classification is presented. They were operated on by an anterior approach and direct fixation of the odontoid process through a screw. There were 13 men and 2 women, the age ranging from 14 to 74 years. The follow up period was from 6 to 36 months (mean 20 months). There was only one complication related to the surgical technique: one screw was misplaced and it was necessary another surgery to replace it. There were no deaths in this series. There were no screw breakdown and the fusion rate was 94%. We propose, based on this study, that the classification of Roy-Camille for odontoid fractures should be always used, since it proposes one surgical approach for each type of fracture. The results of this series show that this technique is useful and has advantages over another modalities of treatment. The correct diagnosis of the type of fracture and an appropriate selection of patients are the main elements to achieve good results.